2021
DOI: 10.1186/s12877-020-01950-9
|View full text |Cite
|
Sign up to set email alerts
|

High percent body fat mass predicts lower risk of cardiac events in patients with heart failure: an explanation of the obesity paradox

Abstract: Background Although high body mass index (BMI) is a risk factor of heart failure (HF), HF patients with a higher BMI had a lower mortality rate than that in HF patients with normal or lower BMI, a phenomenon that has been termed the “obesity paradox”. However, the relationship between body composition, i.e., fat or muscle mass, and clinical outcome in HF remains unclear. Methods We retrospectively analyzed data for 198 consecutive HF patients (76 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 61 publications
2
27
1
1
Order By: Relevance
“…In a cohort of 150 patients hospitalized with HFpEF, higher BMI values were associated with lower mortality (Stavrakis et al, 2013). Consistently, a U-shaped relationship between BMI and mortality has been reported for HFpEF (Kapoor and Heidenreich, 2010;Padwal et al, 2014;Ohori et al, 2021).…”
Section: Obesity Paradoxsupporting
confidence: 59%
See 3 more Smart Citations
“…In a cohort of 150 patients hospitalized with HFpEF, higher BMI values were associated with lower mortality (Stavrakis et al, 2013). Consistently, a U-shaped relationship between BMI and mortality has been reported for HFpEF (Kapoor and Heidenreich, 2010;Padwal et al, 2014;Ohori et al, 2021).…”
Section: Obesity Paradoxsupporting
confidence: 59%
“…The authors found that a lowered BMI may be a significant predictive factor for the frequency of hospitalizations and increased mortality (Nishikido et al, 2019). Similarly, other studies have shown that increased body fat mass, but not appendicular skeletal muscle mass, corresponds to a lower risk of short-term cardiac events in HF patients (Thomas et al, 2019;Ohori et al, 2021). Every 5-unit increase in BMI corresponds to a 10% reduction in mortality (Fonarow et al, 2007).…”
Section: Obesity Paradoxmentioning
confidence: 79%
See 2 more Smart Citations
“…However, changes in SMH with different BMI groups is completely different from the ones in the existing researches [37,38]. Numerous studies have shown that the incidence of chronic diseases is different with different BMI [39]. Therefore, using different methods to calculate skeletal muscle mass parameters has different clinical guidance signi cance.…”
Section: Main Ndings and Comparison With Other Studiesmentioning
confidence: 92%